EVALUATION OF TEACHING FACTORY PROGRAM IN SMK YP IPPI CAKUNG - Sri Utami Purnama SARI; Linda SILVIANA (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2020)
The purpose of this study was to examine the implementation of a teaching factory, and the factors that inhibit its implementation at SMK YP IPPI Cakung. The results of the study noted that the implementation of the teaching factory begins with the establishment of a management structure and collaboration with industry and the related education office. The competency standard used is an application of the school curriculum that is Indonesian National Work Competency Standards (SKKNI) or industry curriculum standard involving students who master vocational competencies and have interests or talents. Thus, the learning media in the form of products have been adjusted to competence. The instructors involved in teaching factory are those who have academic qualifications, experience in industry, and commitment. The products are marketed to consumers and then an evaluation of the implementation of teaching factories are conducted by schools and companies. The inhibiting factors in this program are related to human resources, namely teachers and students. There is still lack of teachers for the department of Computer and Network Engineering but they have fulfilled academic qualifications according to their competencies. In terms of student issues, students' lack of interest and funding are the obstacle. For supporting factors of teaching factory, it includes superior products, which raw materials are easily obtained, and work strategies that can be adapted to conditions. In addition, supporting facilities, good infrastructure, good marketing, and sufficient location are some good things to carry out the production.